Factors that influence students in higher institution using Facebook as a learning tool / Norhayati Mohd Amin - Mohd Amin, Norhayati (2017)
This research investigates the possibilities of integration e-learning with social media to resolve the problem of low interaction among learners and teachers in existing e-learning environments. The problem of this study is lack of e-learning ability to stimulate learners' participation in the course, also unable to have good interaction, where students need to be more pro active instead of being content receiver created and provided by teachers. Even though e-learning has many benefits, but there are also major problems that impact on low usage of e-learning and engage with the course content among students. The study extends the e-Learning Acceptance model, the Unified Theory of Acceptance and Use of Technology (UTAUT) and Technology Acceptance model (TAM) to identify the problem of e-learning and determine the factors that influence students using Facebook as a learning tool instead of e-learning management system. From the research model, four factors are examined that encourage student to use Facebook as a learning tool. The four factors are functionality, accessibility, communication and user experience. Through this study, it helps institution higher learning and lecturer to examine the role of social media in the teaching and learning process. The study participants were among students in higher institution learning in Klang Valley. Data from 222 respondents were collected using questionnaires which has been tested using Cronbach's Alpha, reliability test, descriptive analysis (mean and standard deviation) and multiple regression analysis. Thus, from this result, lack of interaction has been identified as the main problem of e-learning system in order to have efficient learning process. On the other hand, research model has been revised accordingly. The finding indicates that the perceptions regarding the ease of use of Facebook is the key feature that influence students to use the social network for learning purposes. With regards to this finding, accessibility, communication, and user experience are considered as the factors that influence students' intention to use Facebook as a learning tool. A number of recommendations had been highlighted to assist similar studies in future.